THE INFLUENCE OF POLITICAL CULTURE ON STRENGTHENING DEMOCRATIC VALUES IN KAZAKHSTAN - Luzanov Victor (World Scientific Reports, 2024)
The main purpose of the article is to demonstrate the influence of the study of political science on public life, to dwell in more detail on the phenomenon of political culture, which, being the main lever of government at the state level, does not find much popularity among the citizens of Kazakhstan.